The Effect of Forehand Practice on The Wall Media (Department of Physical Education, Sport, Health and Recreation, 2023)
The purpose of this study was to determine the effect of media wall training on the forehand drive in table tennis. The population is 20 people. While the sampling technique was carried out using a total sampling technique, namely the entire population was used as a sample, so that in this study the sample numbered 20 people. The instrument used is The Static Group Pretest-Postest Design. forehand target accuracy. that is, one group was given treatment, but before the treatment was given, an initial test (pretest) was first carried out, then at the end of the treatment a final test (posttest) was carried out with a time of 30 seconds and 3 times the chance. Data analysis techniques using descriptive statistics with t-test. The results showed that the t-count value was greater than the t-table (8.339 > 1.729) so that the t-value obtained in this study was significant. So it can be concluded that the media wall exercise has an influence on the forehand drive in table tennis